2022
DOI: 10.1037/spq0000494
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate practice of consultation communication skills: A randomized controlled trial.

Abstract: Consultation is a key competency area for school psychologists, though much is unknown about how school psychologists develop the competency to consult. Deliberate practice (DP) is a promising approach to enhance use of communication skills, thereby supporting consultation competence. DP training included multiple opportunities for video-recorded consultation practice in response to a consultee’s request for assistance, self-reflection on skill application, and corrective supervisory feedback. In this randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…Research investigating school consultation training is limited. Empirical descriptions of graduate‐level consultation coursework suggest that process skills, including approaches to communication and relationship development, are often not emphasized in training (Hazel et al, 2010; M. L. Newell, 2012; Newman, Villarreal, et al, 2022). One reason may be that there is little research regarding how interpersonal process skills are most effectively taught and scaffolded to guide training (M. Newell & Newman, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research investigating school consultation training is limited. Empirical descriptions of graduate‐level consultation coursework suggest that process skills, including approaches to communication and relationship development, are often not emphasized in training (Hazel et al, 2010; M. L. Newell, 2012; Newman, Villarreal, et al, 2022). One reason may be that there is little research regarding how interpersonal process skills are most effectively taught and scaffolded to guide training (M. Newell & Newman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Newman, Gerrard, et al, 2022; Newman, Villarreal, et al, 2022) applied a deliberate practice (DP) approach to support school psychology graduate students' consultation communication skill development. Consistent with definitions of DP in the literature (i.e., Ericsson & Pool, 2016; Miller et al, 2020; Rousmaniere et al, 2017), the approach included individualized, developmentally appropriate learning objectives for students; supervisor observation, assessment of skill performance, and feedback; and students' successive skill practice and refinement in a simulated situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, several studies indicate that training with a focus on practice and feedback, in contrast to didactic training, leads to better skills in managing client resistance (Westra et al, 2021) and communications skills (Newman et al, 2022). In line with these results, two studies by Perlman et al (2020, 2022) showed that an alliance‐focused and facilitative interpersonal relationship training, based on deliberate practice, had a positive effect on the therapeutic skills of professionals and undergraduates.…”
Section: Introductionmentioning
confidence: 99%
“…True, the current evidence shows DP is more effective than traditional approaches for teaching and training therapists (Barrett-Naylor et al, 2020;Newman et al, 2022;Westra et al, 2021). Still, much remains unknown and subject to revision; for example,…”
mentioning
confidence: 99%